The recent progress of inorganic‐based intelligent responsive nanoplatform for tumor theranostics. Issue 6 (22nd August 2022) - Yang, Zebin; Chen, Hangrong
Abstract: Inorganic nanoplatform exhibits great potentials in drug delivery and responsive release attributed to its inherent physicochemical properties, good biocompatibility, surface modification, and easy synthesis. In this review, the recent progresses on the inorganic smart bio‐responsive nanoplatforms for tumor theranostics are summarized, which could be triggered by either endogenous tumor microenvironment (TME) or the exogenous physical and hopeful to achieve safe, precise, and high efficacy for tumor therapy. Notably, these nanoplatforms generally are dependent on the intelligent and multifunctional design of nanocarriers, including mesoporous silica nanoparticles (MSNs), black phosphorus (BP), Prussian blue (PB), and other inorganic‐based nanoparticles. Finally, the perspectives and challenges of inorganic nanoplatform in the future translational medicine are proposed. Abstract : The recent progresses on the inorganic smart bioresponsive nanoplatforms for tumor theranostics are summarized, including mesoporous silica nanoparticles (MSNs), black phosphorus (BP), Prussian blue (PB), and other inorganic‐based nanoparticles, which could be triggered by either endogenous tumor microenvironment (TME) or the exogenous physical and hopeful to achieve safe, precise, and high efficacy for tumor therapy.